2015
DOI: 10.30970/sbi.0902.413
|View full text |Cite
|
Sign up to set email alerts
|

Activity of ATPases in postmitichondtial fraction of lymphoma NK/Ly cells under bafilomicine and NAADP presence

Abstract: Ключові слова: пухлинні клітини, лімфома NK/Ly мишей, активність АТФ-аз, НААДФ, Na + ,K +-помпа, Са 2+-помпа ПМ і ЕПР. ВСТУП Останнім часом у терапії пухлин значну увагу приділяють таким клітинним "мішеням", як системи активного транспорту йонів [4; 10; 15]. Зокрема, встановлено,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…These data suggested that bafilomycin A1 may inhibit complex I of respiratory chain or α‐ketoglutarate dehydrogenase leading to decrease in mitochondrial oxygen consumption. Effects of bafilomycin A1 on respiration of mitochondria may be related to the fact that mitochondria fraction contains some portion of autophagosomes . We hypothesized that bafilomycin A1 targeting H + ‐ATPase can acidify extramitochondrial volume and decrease the Ca 2 + uptake by mitochondria.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These data suggested that bafilomycin A1 may inhibit complex I of respiratory chain or α‐ketoglutarate dehydrogenase leading to decrease in mitochondrial oxygen consumption. Effects of bafilomycin A1 on respiration of mitochondria may be related to the fact that mitochondria fraction contains some portion of autophagosomes . We hypothesized that bafilomycin A1 targeting H + ‐ATPase can acidify extramitochondrial volume and decrease the Ca 2 + uptake by mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondria present a unique set of key intracellular functions such as ATP synthesis, production of ROS, and Ca 2 + buffering. It has to be pointed that “unwashed” mitochondrial suspension used in this work contains several other subcellular organelles such as autophagosome and other . It is not surprising because autophagy has important role in selective elimination of damaged mitochondria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Assay of ATPase activity. ATPase activity was determined according to the content of orthophosphate that was released after ATP hydrolysis [8,9]. At the beginning of the experiment 200 μlof post-mitochondrial subcellular fraction of patients' colon mucous was transferred to a standard incubation medium containing (mM) NaCI -50.0; KCI -100.0; Tris-НСІ -20.0; MgCI 2 -3.0; CaCI 2 -0.01; рН 7.4 at 37 °С.…”
Section: Methodsmentioning
confidence: 99%